Economic Factors that Affect the Technical Efficiency Index of the Public Hospitals of the State of Nariño -Colombia 2008-2014 - Portillo Melo, Danyeli Maricel; Enriquez Guerra, Francely Brigit; Riascos Hermoza, Julio César (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper analyzes the economic factors that affect the relative technical efficiency indexes of the public hospitals of the state of Nariño between 2008 and 2014. In this study, the TEI were calculated through data envelopment analysis (DEA) that evaluates the productive and relative performance of each hospital. The results indicate that, on average, 38.27% of hospitals operate efficiently from a product-oriented approach. Finally through econometrics models with panel data and fixed effects, the paper suggest that the potential demand, the hospital services portfolio and the installed capacity, explains the variations of the technical efficiency measurements obtained.